HUBUNGAN SELF-ESTEEM DENGAN TINGKAT STRES AKADEMIK SISWA SMA NEGERI 1 INDRALAYA - Tiana Febriani; Minarsi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Self-esteem plays an important role in students’ lives as it influences how they deal with various academic demands that may potentially cause stress. This study aims to examine the relationship between self-esteem and academic stress among students of SMA Negeri 1 Indralaya. This research employed a quantitative approach with a correlational method. The population consisted of all 360 students of grade XI, with a sample of 78 students determined using Slovin’s formula. The sampling technique used was Simple Random Sampling with the help of a picker wheel. Data were collected through psychological scales, namely the self-esteem scale and the academic stress scale. The results of the study indicated that the majority of students’ self-esteem levels were in the moderate category with a percentage of 38.5% (30 students), while academic stress levels were also mostly in the moderate category with a percentage of 44.9% (35 students). Hypothesis testing using the product moment correlation formula obtained a correlation coefficient (r) of -0.685 with a significance value of 0.000 (< 0.05). This finding shows a significant negative relationship between self-esteem and academic stress among students of SMA Negeri 1 Indralaya. In other words, the higher the students’ self-esteem, the lower the level of academic stress experienced, and vice versa. The results of this study are expected to serve as a reference for schools, especially guidance and counseling teachers, in designing programs or services aimed at enhancing students’ self-esteem so they can better manage academic stress.